(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
Fish farming in Armenia leads to the introduction of alien fish species such as Prussian carp (Carassius gibelio) and Stone moroko (Pseudorasbora parva). Given their rapid spread throughout Armenia, it became necessary to investigate their spatio-temporal distribution patterns to develop some monitoring tools and conservation strategies for the stocks of native species. Thus, we created a comprehensive database through literature reviews, structured interviews with scientists, and open-source data. Our analysis revealed an increasing frequency of records as ichthyological studies intensified. These invasive species are now encountered in nearly all regions of Armenia, with altitude being the only limiting factor, probably due to water temperature.